Investigation of a novel separately-configured thermoelectric cooler: A pathway toward the building integrated thermoelectric air conditioning - Haowen Liu; Limei Shen; Yunhai Li; Xudong Zhao; Guiqiang Li; Zeyu Liu; Hongxing Yang (Advances in Applied Energy)
Due to structural limitations, the hot and cold sides of conventional thermoelectric coolers (TECs) are fully integrated, making it challenging to directly incorporate TECs into building facades or ceilings to utilize natural ventilation from the building exterior assisting cooling the hot junction. This constraint renders TECs unsuitable for direct application in building façade. To overcome these challenges, an innovative separately-configured thermoelectric cooler (SC-TEC) has been developed. This original design enables the direct integration of TECs into building façades for air conditioning while utilizing the outdoor environment as auxiliary cooling for the TEC's hot side, thereby enhancing overall system performance. Our preliminary study showed that, in a TECs-ceiling system, the novel SC-TEC achieves a 13 % higher cooling capacity compared to a traditional TEC-ceiling. The unit cooling output increased from 16.66 W/m² to 18.82 W/m². And the temperature profiles shows that the cooling capacity of the SC-TEC could be further enhanced with a higher-performance connecting material. Given its advantages, such as no moving parts, noiseless operation, and efficient heat transfer, the SC-TEC has potential to open up new research direction in the building-TEC sector.